(untitled) (Revue Africaine des Sciences Sociales et de la Santé Publique, 2023)
Yellow fever is a notifiable disease. It is likely to cause epidemic outbreaks with high mortality. The fatality rate can vary between 25% and 50%. The World Health Organization (WHO) estimates the number of cases at 200,000 each year, with the majority on the African continent. The preventive measures available to countries have largely proven their effectiveness. In Mali, on December 5, 2019, the Government officially declared an outbreak of yellow fever in two highly populated regions of the country, Sikasso and Koulikoro. It is in this context that we conducted this descriptive cross-sectional study. The general objective was to evaluate the yellow fever epidemiological surveillance system from January 1, 2020 to December 31, 2020 in the Kadiolo Health District. The evaluation of the epidemiological surveillance system for yellow fever in the health district of Kadiolo made it possible to verify the capacities of this district to deal with the occurrence of possible outbreaks. The epidemiological surveillance indicators assessed were good overall.